30th IEEE International Performance Computing and Communications Conference 2011
DOI: 10.1109/pccc.2011.6108110
|View full text |Cite
|
Sign up to set email alerts
|

Best-effort authentication for opportunistic networks

Abstract: Abstract-Prior work has shown that uncontrolled messaging in ad-hoc opportunistic networks results in a disproportionate sharing of network capacity. Solutions based on publicly verifiable sender authentication mechanisms, such as those in [1], require complete message transmission for proper verification. However, introducing message fragmentation, e.g., to optimize limited transmission opportunities, could negatively impact resource management. Unverifiable message fragments that are assigned lower prioritie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…J. Solis et al [70] suggested using "best-effort" authentication, a method that accepts false positives but not false negatives, easier to break than the Merkle hash tree-based techniques, requiring fewer computations for benign nodes' fragment authentication by intermediaries in Opportunistic Networks. The study suggested that "best-effort" authentication is only for fragment authentication and should not replace traditional end-to-end message authentication.…”
Section: B Oppnets Authentication Schemesmentioning
confidence: 99%
“…J. Solis et al [70] suggested using "best-effort" authentication, a method that accepts false positives but not false negatives, easier to break than the Merkle hash tree-based techniques, requiring fewer computations for benign nodes' fragment authentication by intermediaries in Opportunistic Networks. The study suggested that "best-effort" authentication is only for fragment authentication and should not replace traditional end-to-end message authentication.…”
Section: B Oppnets Authentication Schemesmentioning
confidence: 99%
“…OppNets are used to communicate between the nodes which may be mobiles or other devices having Wi-Fi or Bluetooth using personal laptops, cameras, sensors. OppNets may connect to other heterogeneous networks among the cellular base station, sensor networks, IoT devices, and other networks which connected through WI-FI [1,2,3,4]. In this network the nodes act to each other as a router that causes Opportunistic networks to be more adaptable than Delay Tolerant Network (DTN) as shown in Fig.…”
mentioning
confidence: 99%